Prognostic value of laboratory and radiological parameters in kerosene poisoning - Kulkarni, Venu; K., Dhanalakshmi; K., Raju; P., Megha (International Journal of Contemporary Pediatrics, 2019)
Background: Kerosene poisoning, a commonly encountered situation in pediatric emergencies, caused varied systemic manifestations ranging from asymptomatic state to altered sensorium and cardiac arrhythmias. Gupta score has been traditionally used to prognosticate such cases. Limited number of studies have been done previously despite high incidence rates pertaining to laboratory and radiological features. Present study aimed to determine association between these features and outcome in terms of duration of stay. Methods: A retrospective study consisted of all children presented with kerosene poisoning from May 2017 to May 2018. CBC was done within 12 hours of presentation and CXR was taken after 6 hours of exposure. These values were compared against duration of stay to predict prognosis. Results: Most children were in age group of 1-3 years, male predominance 62.9%. Quantity of consumption didn’t have any effect on outcome. Large proportion of children were asymptomatic 60%, followed by hurried breathing 31.5% - most frequent presenting complaint. Peak duration of consumption was 4 pm to 8 pm. CBC parameters- Hemoglobin status and WBC counts failed to have correlation with outcome in terms of duration of stay. CXR taken after 6 hours exposure- was imperative to predict outcome. Conclusions: Radiological features on CXR in addition to clinical symptoms could be used to decide likely outcome after kerosene consumption.